Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Ardi Subakti; Subakti, Ardi; Rofiqoh, Ifah (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2025)
This study aims to examine the effect of sustainability report disclosure, which includes economic, environmental, and social performance, on financial performance as proxied by Return on Assets (ROA) in companies listed on the LQ45 Index for the 2020-2023 period. The data used are secondary data obtained from financial reports and sustainability reports. The sampling technique employed is purposive sampling, with a final sample size of 88 for the 2020-2023 period. The data analysis method in this research is moderation regression analysis with panel data using Eviews 12. The results show that the disclosure of sustainability reports covering economic, environmental, and social performance has no significant partial effect on financial performance (ROA). Managerial ownership can moderate the influence of environmental performance disclosure on financial performance (ROA) but cannot moderate the influence of economic and social performance disclosure on financial performance (ROA). The implication of this research is that companies may consider increasing managerial ownership to encourage sustainable practices, as managers who are also owners of the company tend to have a direct interest in achieving positive financial performance.